"Simultaneous immersion": How online postgraduate study contributes to the development of reflective practice among public service practitioners. Issue 7 (2nd October 2016) - Brooks, Sally; Roberts, Ellen
Abstract : This paper examines how the process of engaging simultaneously in study and work – through online distance-based study – affects students' capacity to apply their learning in and for the workplace. The paper takes as its starting point the importance of extending notions of "educational effectiveness" beyond course-based attainment to encompass the impact of learning within the workplace. It explores the interface between study and work, focusing on the case of online postgraduate programmes in public management at the University of York. It finds that simultaneous immersion in study and work can create the conditions for "public reflection" that underpin work-based learning and that a key factor is the student-practitioner's ability to mobilise "episodic power." The paper suggests ways in which existing approaches to online postgraduate learning might be enhanced in order to capitalise on these conditions of simultaneous immersion.